Comparison of the accuracy of conventional impression technique and an intraoral scanning system after crown preparation in canine teeth of dogs: a cadaver study - Metje, Benjamin; Gawor, Jerzy Pawel; Lüpke, Matthias; Meller, Sebastian; Schreyer, Jan (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to compare digital impressions obtained by an intraoral scanner (IOS) with the dimensions of the corresponding stone model produced from conventional impressions and the original tooth to assess the accuracy of IOS in veterinary dentistry.MethodsIn this cadaver study, 40 canine teeth of dogs underwent standard crown-preparation. For each specimen, both conventional impressions with subsequent stone model fabrication and digital impressions were obtained. The surfaces of the stone replicas and the original teeth were scanned, and the distance between the stone model surface and the original tooth surface, as well as the surface of the intraoral scan and the original tooth surface, was compared. Mean and median surface deviations were computed in millimeters using a 3D surface comparison tool of Amira 3D Pro software (Thermo Fisher Scientific, Waltham, Massachusetts, USA).ResultsEven though the deviations between the stone models and the original teeth were lower compared to the ones between digital impressions and the original teeth in both mean and median, no significant differences in the deviations from the original tooth between both modalities were detected (p = 0.4721 for mean values, p = 0.4129 for median values).ConclusionThe observed deviations between digital and conventional impression techniques were minimal and fell within clinically acceptable thresholds as defined in human dentistry literature. These results indicate that this IOS system could provide a reliable and accurate alternative for capturing crown-prepared canine teeth in dogs compared to the currently used standard technique.